PENGARUH KUALITAS DAN DESAIN PRODUK TERHADAP BRAND SWITCHING HANDPHONE (Studi pada Mahasiswa STIE Lampung Timur) - Sulastri, Susi (DINAMIKA (Jurnal Manajemen Akutansi Bisnis dan Kewirausahaan), 2020)
The purpose of this study was to analyze the influence of quality and product design on brand switching of mobile phones at STIE Lampung Timur Students. The population in this study were BPJS Kesehatan patients who had experienced the services of the Sukadana Community Health Center, Sukadana District. The number of population used in this study were 218 people and the sample taken was 100 students. The sampling technique used simple random sampling technique. In processing the data, this study uses the SPSS program. This study uses multiple linear analysis. This analysis is used to examine the relationship between the independent variable and the dependent variable. The results showed that the variable Product Quality and Product Design simultaneously had a significant positive effect on Mobile Brand Switching. The results of this study indicate that the determinant coefficient value of R = 0.929, this value means that the level of the relationship between Product Quality and Design on Brand Switching is strong. While the value of R square is 0.987, the value of R square can be called the coefficient of determination which means that Brand Switching is influenced by Product Quality and Product Design by 98.7% while the rest is influenced by other factors not examined in this study. Product quality has a significant effect on the Mobile Brand Switching of STIE East Lampung Students, as evidenced by the t test where the significance value is 0.00 <0.05. Product design has a significant effect on the Mobile Brand Switching of STIE East Lampung Students, as evidenced by the t test where a significance value of 0.00 <0.05 is obtained. So that Ha is accepted and Ho is rejected, which means that there is an effect of product quality and product design on the Mobile Brand Switching of STIE East Lampung students.